Analysis of cis-regulatory changes underlying phenotype divergence shaped by domestication in pigs - Liu, Chunpeng; Ao, Na; Liang, Yuwen; Ma, Tingting; Wang, Qishan; Wang, Zhen; Wu, Fen; Zhang, Zhenyang; Fang, Yifei; Wang, Minghui; Pan, Yuchun; Fu, Jing (Frontiers in Genetics, 2024)
Background Cis-regulatory elements (CREs) are regions of DNA that regulate the expression of nearby genes. Changes in these elements can lead to phenotypic variations and adaptations in different populations. However, the regulatory dynamics underlying the local adaptation of traits remain poorly understood in Chinese and Western pigs. By comparing the chromatin accessibility profiles of skeletal muscle, liver, and fat between these two pig populations, we aimed to identify key regulatory elements that could explain phenotypic differences observed between the two groups. Results Our results revealed that the genome-wide chromatin accessibility profiles were largely similar at a qualitative level within tissues. However, we also identified local regions that exhibited quantitative differences, most of which occurred in liver tissue. Interestingly, we found that most of the increased chromatin accessibility in the livers of Chinese pigs was associated with tissue-specific openness. Furthermore, we observed a positive correlation between the ATAC-seq signal at the transcript start site (TSS) and the expression levels of nearby genes. Motif enrichment analysis revealed NR2F1 as a key regulator in Chinese pigs. Differentially expressed genes (DEGs) in Chinese pigs showed enrichment for NR2F1 response targets. One of the genes regulated by NR2F1 in Chinese pigs, NPC1, harbored a high alternative allelic frequency in the intron region. Conclusion Overall, our study provides valuable insights into the regulatory dynamics underlying phenotypic variation in pigs. By elucidating the role of CREs in driving phenotypic variation, we can better understand the genetic basis of complex traits and potentially identify targets for genetic improvement in livestock breeding programs.